Arrival infrastructures. Migration and urban social mobilities. - (:unkn) unknown (Palgrave Macmillan, 2019)
This volume introduces a strategic interdisciplinary research agenda on arrival infrastructures. Arrival infrastructures are those parts of the urban fabric within which newcomers become entangled on arrival, and where their future local or translocal social mobilities are produced as much as negotiated. Challenging the dominance of national normativities, temporalities, and geographies of "arrival," the authors scrutinize the position and potential of cities as transnationally embedded places of arrival. Critically interrogating conceptions of migrant arrival as oriented towards settlement and integration, the volume directs attention to much more diverse migration trajectories that shape our cities today. Each chapter examines how migrants, street-level bureaucrats, local residents, and civil society actors build-with the resources they have at hand-the infrastructures that accommodate, channel, and govern arrival.
Keywords: Sozialwesen; Einwanderung; Sozialinfrastruktur; Wohnen; Stadtsoziologie; Integration; Geschichte; Sozialgeschichte; Flüchtling; Asylbewerber; Temporäres Wohnen; Flüchtlingspolitik; Nichtregierungsorganisation; Soziales Netzwerk; Städtevergleich; Internationaler Vergleich